Psychological Empowerment and Work Engagement as predictors of Work Satisfaction: A sample of Hotel Employees - Moura, Daniel; Orgambídez-Ramos, Alejandro; de Jesus, Saul Neves (Journal of Tourism, Sustainability and Well-being, 2015)
With more organizations looking for employees who take initiative and respond creatively to the challenges of the job, engagement and psychological empowerment becomes important at both individual and organizational levels. Engaged employees are generally more satisfied with their work, committed and effective at work. According to the JDR model (Schaufeli and Bakker, 2004), engagement may be produced by two types of working conditions: job demands (i.e., role stress) and job resources (i.e., psychological empowerment; self-efficacy). This study examines the role of psychological empowerment and work engagement as antecedents of job satisfaction. A cross sectional study using online questionnaires was conducted. The sample consisted of 152 Portuguese workers in hotels. Tourism is an important tool for profit and the Portuguese hotels are fundamental for the growth of the country. Employee satisfaction increases employee retention and increases productivity influencing the income / profits for hotels. Hierarchical multiple regressions analyses revealed that job satisfaction was significantly predicted by psychological empowerment and work engagement. Results support JDR model by showing that positive outcomes, such as job satisfaction, may be predicted by motivational process and job demands. On a practical level, JDR model provides a framework for understanding motivating workplaces and engaged and satisfied hotel employees.